2017
DOI: 10.1093/pch/pxx116
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obesity are associated with lower vitamin D status in Canadian children and adolescents

Abstract: This study confirms the inverse association between adiposity and serum concentrations of 25-hydroxyvitamin D in Canadian youth and the independent association of overweight/obesity to 25-hydroxyvitamin D level and vitamin D status after adjustment for other factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
22
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 26 publications
10
22
0
4
Order By: Relevance
“…It has been established that the level of low income per family member increases by 1.31 times the likelihood of vitamin deficiency in adolescents (p = 0.015). The findings confirm the results of other studies conducted in different countries, but in our case, the risk ratio was 1.36, while in the USA it was 1.6 13 , and in Canada 3.14 14 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…It has been established that the level of low income per family member increases by 1.31 times the likelihood of vitamin deficiency in adolescents (p = 0.015). The findings confirm the results of other studies conducted in different countries, but in our case, the risk ratio was 1.36, while in the USA it was 1.6 13 , and in Canada 3.14 14 .…”
Section: Discussionsupporting
confidence: 92%
“…The data obtained during the study showed a similar trend of change in the status of vitamin D in children of different ages during epidemiological studies in Ukraine, but were lower compared with the data of the studies in the USA, Spain, and Italy 5,9 . Researchers explain the low levels of 25 (OH) D in blood serum by depositing calcidiol in the adipose tissue, reducing bioavailability, and reducing its synthesis under the influence of ultraviolet rays 14 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are scientific papers presenting results similar to ours, published by many researchers, who indicate that vitamin D deficiency is most prevalent among children suffering from overweight and obesity [12][13][14]. It is believed that with excessive amounts of adipose tissue the sequestration of calcidiol increases within it, resulting in vitamin D deficiency [8,12].…”
Section: Discussionsupporting
confidence: 73%